DATA STORAGE AND PRIVACY IN AI SYSTEMS FOR RISK IDENTIFICATION AND PERSONALIZED INTERVENTIONS IN SPECIAL EDUCATION - Shakhnoza Khaydarova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Artificial Intelligence (AI) has transformed education, especially in identifying risks of disabilities and recommending personalized treatments and Individualized Education Programs (IEPs) for students with learning disabilities. While the potential of AI in special education is immense, challenges surrounding data storage and privacy pose significant concerns. This article explores the intersection of AI-driven educational technologies, data privacy regulations, and secure data storage solutions, offering insights into ethical frameworks and best practices to mitigate privacy risks while maximizing the benefits of AI.